2021
DOI: 10.1155/2021/9210817
|View full text |Cite
|
Sign up to set email alerts
|

Green versus Chemical Precipitation Methods of Preparing Zinc Oxide Nanoparticles and Investigation of Antimicrobial Properties

Abstract: Comparison of green and chemical precipitation method syntheses of zinc oxide nanoparticles (ZnO NPs) was performed, and antimicrobial properties were investigated. Avocado, mango, and papaya fruit extracts were carried out for the green synthesising methods, while the chemical precipitation method was chosen from chemical synthesis methods. Zinc nitrate was used as a salt precursor, whereas leaf extract was served as a reducing agent for green synthesising methods. In addition, sodium hydroxide, polyvinyl alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…A promising aspect is the presence of phytoactive compounds in the NPs structure which can promote its additional properties ( 76 ). However, few studies compared these two means of synthesis, and some of them showed evidence that green synthesized ZnNPs even had lower antimicrobial effect ( 77 , 78 ). Moreover, disadvantages of the green synthesis include poor control of NPs formation, difficulty in large-scale production and differences in compound composition in plant extracts ( 79 ).…”
Section: Znnps As a Prospective Antimicrobial Agentmentioning
confidence: 99%
“…A promising aspect is the presence of phytoactive compounds in the NPs structure which can promote its additional properties ( 76 ). However, few studies compared these two means of synthesis, and some of them showed evidence that green synthesized ZnNPs even had lower antimicrobial effect ( 77 , 78 ). Moreover, disadvantages of the green synthesis include poor control of NPs formation, difficulty in large-scale production and differences in compound composition in plant extracts ( 79 ).…”
Section: Znnps As a Prospective Antimicrobial Agentmentioning
confidence: 99%
“…The precipitation method has been used extensively to prepare ZnO NPs [ 9 , 10 , 11 , 12 , 13 , 14 ]. Recently, Lam et al synthesized iron-doped ZnO (Fe-ZnO) nanoparticles according to a simple and green method utilizing Hibiscus rosa-sinensis leaf extract, reporting the properties of these nanoparticles for the inactivation of Escherichia coli ( E. coli ) under sunlight irradiation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication of curcumin-capped zinc oxide nanoparticles (ZnO NPs). Curcumin-capped zinc oxide nanoparticles have been prepared via the chemical reduction method of zinc precursors (Zn 2+ ) via phenolic groups present in Curcuma longa extract, as reported previously [42][43][44] with minor modications. Typically, 25 ml of 4 mM of ethanolic solution of Zn(CH 3 COO) 2 was added to 75 ml of curcumin ethanolic extract under vigorous stirring and reux at 70 C for 2 h. The reaction colour changed from orange to yellowish precipitate, indicating the formation of Zn(OH) 2 powder.…”
Section: Methodsmentioning
confidence: 99%